Navigating geopolitical shifts and turbulence: a multifaceted analysis of international relations - Zarina Othman,; Bakri Mat,; Muhammad Danial Azman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The year 2023, which is about to draw its curtain, has recorded various geopolitical changes and challenging issues due to complex interactions among various parties, which require a thorough solution for the benefit of humanity. The events of the Russia-Ukraine War, the conflict in the Middle East that is heating up, in addition to climate change that results in various catastrophes are among some bitter facts as a hard lesson for all of us. Parallel to this development, this edition of SINERGI covers a wide range of topics, such as the US-China competition and democratic leadership in the context of ASEAN, as well as China’s Belt and Road Initiative and its effects on Kazakhstan and Turkmenistan. The collection also examines the geopolitical significance of locations such as the Strait of Hormuz and reassesses historical personalities like the case of the Empress Dowager Cixi. Overall, this compilation provides valuable, insightful information about the intricacies of international politics, economic manoeuvres, and regional security, which presenting a wide range of viewpoints to guide scholarly discussion and policy.